Study on Cutaneous Manifestations of Leukemia and Lymphoma - Wahab, Md Abdul; Haque, AKM Rejaul; Khan, Md Rafiquzzaman; Hassan, Biswas Shaheen; Rahman, Md Moksedur; Rahman, M Hasibur; Islam, Md Aminul; Khatun, Masuda; Kumar, Saha Bijoy (Community Based Medical Journal, 2015)
Leukemia and Lymphoma can present with various cutaneous manifestations. These include specific cutaneous diseases and non-specific cutaneous lesions. Non-specific skin lesions are more common in patients with Hodgkins diseases. Leukemia cutis (specific skin lesions of Leukemia) most commonly occurs concommitent with or following the diagnosis of leukemia. The skin may also be the site of relapse of Leukemia after chemotherapy. Uncommonly leukemia cutis may be identified while the bone marrow and peripheral blood are normal. Those patients are classified as aleukemic leukemia cutis. The objective of this study is to know the prevalence of skin manifestations of hematologic malignancies and to help the diagnosis and management of hematologic malignancies in some extent. It is a cross sectional observational study in which the skin lesions of the patients in hematologic malignancies who were already diagnosed & hospitalized in the hematology department of Bangabandhu Sheikh Mujib Medical University were evaluated in the period of one year. We found malignant infiltrative lesions & hemorrhagic findings both were predominate in leukemia. Infections were predominant in both Leukemia & Lymphoma. CBMJ 2015 July: Vol. 04 No. 02 P: 31-34